Comparative content analysis of professional, semi-professional, and user-generated restaurant reviews. Issue 5 (20th October 2017) - Parikh, Anish A.; Behnke, Carl; Almanza, Barbera; Nelson, Doug; Vorvoreanu, Mihaela
ABSTRACT: This study examines the content of professional, semi-professional, and user-generated reviews. By comparing these three review types, this study was able to identify characteristics and factors unique to each type of review. Although, the amount of discourse in a particular factor varied, food is clearly the most important review factor regardless of review type. Semi-professional reviews emphasize atmosphere and décor more than both newspaper and user-generated reviews, while price factors were more prevalent in semi-professional reviews and user-generated reviews than in newspaper reviews. Understanding the varied structures of review types provides guidance for both restaurateurs and review users.